Cytosolic nucleic acid sensors and interferon beta-1 activation drive radiation-induced anti-tumour immune effects in human pancreatic cancer cells - Kerschbaum-Gruber, Sylvia; Kleinwächter, Ava; Popova, Katerina; Kneringer, Alexandra; Appel, Lisa-Marie; Stasny, Katharina; Röhrer, Anna; Dias, Ana Beatriz; Benedum, Johannes; Walch, Lena; Postl, Andreas; Barna, Sandra; et al. (Frontiers in Immunology, 2024)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) remains a leading cause of cancer-related deaths worldwide with limited treatment options due to extensive radiation and chemotherapy resistance. Monotherapy with immune checkpoint blockade showed no survival benefit. A combination of immunomodulation and radiotherapy may offer new treatment strategies, as demonstrated for nonsmall cell lung cancer. Radiation-induced anti-tumour immunity is mediated through cytosolic nucleic acid sensing pathways that drive the expression of interferon beta-1 (IFNB1) and proinflammatory cytokines.Methods: Human PDAC cell lines (PANC-1, MIA PaCa-2, BxPC-3) were treated with X-rays and protons. Immunogenic cell death was measured based on HMGB1 release. Cytosolic dsDNA and dsRNA were analysed by immunofluorescence microscopy. Cell cycle progression, MHC-I and PD-L1 expression were determined by flow cytometry. Galectin-1 and IFNB1 were measured by ELISA. The expression levels and the phosphorylation status of the cGAS/STING and RIG-I/MAVS signalling pathways were analysed by western blotting, the expression of IFNB1 and proinflammatory cytokines was determined by RT-qPCR and genome-wide by RNA-seq. CRISPR-Cas9 knock-outs and inhibitors were used to elucidate the relevance of STING, MAVS and NF-κB for radiation-induced IFNB1 activation.We demonstrate that a clinically relevant X-ray hypofractionation regimen (3x8 Gy) induces immunogenic cell death and activates IFNB1 and proinflammatory cytokines. Fractionated radiation induces G2/M arrest and accumulation of cytosolic DNA in PDAC cells, which partly originates from mitochondria. RNA-seq analyses shows a global upregulation of type I interferon response and NF-κB signalling in PDAC cells following 3x8 Gy. Radiation-induced immunogenic response is regulated by STING, MAVS and NF-κB. In addition to immunostimulation, radiation also induces immunosuppressive galectin-1. No significant changes in MHC-I or PD-L1 expression were observed. Moreover, PDAC cell lines show similar radiation-induced immune effects when exposed to singledose protons or photons.Our findings provide a rationale for combinatorial radiation-immunomodulatory treatment approaches in PDAC using conventional photon-based or proton beam radiotherapy.